Exploring Student Experiences in E-Learning for English Literacy: Voices from an Indonesian Higher Education Context - Amrang, Amrang; Isma, Adi; Rusdiah, Rusdiah; Ridwan, Ridwan (English Education Department at FKIP Nommensen University, 2025)
This qualitative case study explored students' experiences and responses towards the implementation of e-learning in English literacy classes at Universitas Sulawesi Barat, Indonesia. The study employed a purposive sampling method, involving 145 students enrolled in reading and writing courses during the 2022/2023 academic year. Data were collected through reflection essays addressing 30 questions, validated by subject matter experts, and analyzed using thematic analysis. The findings revealed several key themes, including challenges faced by students such as internet connectivity issues and initial difficulties navigating e-learning systems. While e-learning facilitated ubiquitous learning, concerns were raised regarding engagement levels, social connectedness, and comprehension compared to face-to-face interactions. Students valued the flexibility and accessibility of e-learning resources but emphasized the need for relevant, reliable, and interactive materials. The study underscored the valuable role of technology in enhancing e-learning quality through expansive content access, interactive features, and flexibility. However, digital literacy gaps and suitability concerns for certain skills were identified as limitations. Overall, a balanced blended learning approach integrating e-learning with traditional face-to-face elements was recommended to optimize learning outcomes in English literacy education. The findings inform pedagogical practices, institutional strategies, and future research on leveraging educational technology to enhance English literacy instruction effectively.